Dissipative Dynamic Libraries (DDLs) and Dissipative Dynamic Combinatorial Chemistry (DDCC). Issue 6 (23rd September 2022) - Del Giudice, Daniele; Spatola, Emanuele; Valentini, Matteo; Ercolani, Gianfranco; Di Stefano, Stefano
Abstract: This Concept is focused on the key features of dissipative dynamic combinatorial chemistry (DDCC). DDCC deals with transient libraries of compounds, maintained out‐of‐equilibrium by the consumption of a fuel, whose composition changes upon the selection pressure of kinetic and/or thermodynamic processes. Concepts and definitions of kinetic and thermodynamic dissipative dynamic libraries ("KDDL" and "TDDL"), are introduced and illustrated by a number of actual cases, thus showing the consistency of the present approach. Such concepts and definitions can help establish a common language for this emerging field, which, in our view, has the potential to become highly relevant to supramolecular chemistry. Abstract : Dissipative Dynamic Libraries : In this Concept, the fundamental features of Dissipative Dynamic Libraries (DDLs) maintained out‐of‐equilibrium by the consumption of a fuel are described with particular emphasis on the factors that govern the composition of the libraries over time.